2007
DOI: 10.1177/156482650702800204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Daily versus Once-Weekly Home Fortification with Micronutrient Sprinkles on Hemoglobin and Iron Status among Young Children in Rural Bangladesh

Abstract: Background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 30 publications
3
45
1
2
Order By: Relevance
“…Al respecto, se ha evaluado diferentes estrategias para lograr una mayor adherencia, como incrementar el tiempo de exposición pero con dosis flexibles para asegurar cubrir la deficiencia de hierro (23) o tener solo una toma semanal pero a altas dosis (24,25) , situaciones que podrían ser evaluadas en nuestro contexto.…”
Section: Discussionunclassified
“…Al respecto, se ha evaluado diferentes estrategias para lograr una mayor adherencia, como incrementar el tiempo de exposición pero con dosis flexibles para asegurar cubrir la deficiencia de hierro (23) o tener solo una toma semanal pero a altas dosis (24,25) , situaciones que podrían ser evaluadas en nuestro contexto.…”
Section: Discussionunclassified
“…However, all mothers were instructed not to give more than one sachet a day. The content of Sprinkles sachets was identical for all groups and included 12.5 mg elemental iron as microencapsulated ferrous fumarate, 5 mg zinc as zinc gluconate, 300 mg retinol equivalents as retinol acetate, 160 mg folic acid and 50 mg vitamin C. The rationale for delivering 60 sachets to all children was based on the demonstrated efficacy of a twomonth daily supply of Sprinkles (Zlotkin et al, 2001(Zlotkin et al, , 2003Hirve et al, 2007;Hyder et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…For example, a recent field trial in India showed that a daily iron dose of 12.5 mg given as Sprinkles over a two-month period significantly increased haemoglobin concentrations and successfully treated anaemia (Hirve et al, 2007). In a recent study in Bangladesh, focus group discussions revealed that mothers preferred a less structured regimen than daily use (Hyder et al, 2007). Mothers reported that a prescribed dosing regimen, whether daily or onceweekly was rigid and imposed psychological stress if a scheduled dose was inadvertently missed.…”
Section: Introductionmentioning
confidence: 99%
“…Kaliganj is a fair representation of rural Bangladesh with its high population density, fertile agricultural land, susceptibility to seasonal flooding, and limited access to health-care and education services. Similar to other rural settings of Bangladesh, the study area is known to have widespread malnutrition and poverty, with women and children bearing most of the burden (29,30) . Kaliganj is not an area with endemic malaria or hookworm (hookworms affect fewer than 2 % of children under the age of 2 years), but it does have a high prevalence of IDA (approximately 87 %) among children 6 to 24 months of age (29)(30)(31) .…”
Section: Study Area and Participantsmentioning
confidence: 99%
“…However, the original Sprinkles MNP formulation did not contain Ca because of the postulated negative effect on Fe absorption (29) . In the current study, we used a new Sprinkles MNP formulation which included Ca in addition to Fe, Zn, folic acid, ascorbic acid and vitamin A.…”
mentioning
confidence: 99%